2002
DOI: 10.1021/jp012602q
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Mechanical Investigation of the Relation between Impact Sensitivity and the Charge Distribution in Energetic Molecules

Abstract: Quantum mechanically determined electrostatic potentials for isosurfaces of electron density of a variety of CHNO explosive molecules are analyzed to identify features that are indicative of sensitivity to impact. This paper describes the development of models for prediction of impact sensitivity of CHNO explosives using approximations to the electrostatic potentials at bond midpoints, statistical parameters of these surface potentials, and the generalized interaction properties function [J. S. Murray, T. Brin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
436
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(458 citation statements)
references
References 77 publications
15
436
0
3
Order By: Relevance
“…[30][31][32][33][34] A quantitative structure-property relationship (QSPR) study was used by Wang et al [35] for prediction of impact sensitivity of nitramine, and a set of 35 molecular descriptors were calculated to represent its molecular structure. It was found that tunneling occurred from the ground state to excited states during the explosion of benzenoid molecules initiated by impact.…”
Section: Molecular Properties and Micromechanics Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32][33][34] A quantitative structure-property relationship (QSPR) study was used by Wang et al [35] for prediction of impact sensitivity of nitramine, and a set of 35 molecular descriptors were calculated to represent its molecular structure. It was found that tunneling occurred from the ground state to excited states during the explosion of benzenoid molecules initiated by impact.…”
Section: Molecular Properties and Micromechanics Methodsmentioning
confidence: 99%
“…[42] However, it is still necessary and useful to carry out correlation studies to identify molecular properties that indicate impact sensitivity. [43] In fact, Chen and Cheng [44] discovered a relationship between the electronic properties (band gap) of cis-1,3,4,6-tetranitrooctahydroimidazo- [4,5-d]imidazole (BCHMX) and its impact sensitivity. Besides, according to Zeman, [45] Huang, [46] and Wang, [47,48] impact sensitivity is also dependent on the electrotopological state indices.…”
Section: Molecular Properties and Micromechanics Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely used in biology [13,14], toxicology [15,16] and drug design [17,18], their applications for physico-chemical properties increased since many years [19,20], particularly for the properties of energetic materials [21][22][23][24][25][26][27][28][29][30][31][32]. Their principle consists in developing a mathematic relationship connecting a macroscopic property of a compounds series to microscopic descriptors derived from their molecular structures, using a reliable experimental data set.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, large errors present in some of experimental data also hamper for explosives scientists to find a good correlation between some of specific molecular descriptors and the impact sensitivity of energetic molecules. [4][5][6][7] Although some scientists report successes in finding a reasonable correlation between them, this appears to be only possible in a certain molecular type with a small number of energetic molecules. Thus, if one wants to derive a predictive methodology for impact sensitivity to cover various types of energetic molecules, neural networks (NN) may be a good choice in current circumstances.…”
Section: Introductionmentioning
confidence: 99%